Consumers’ Willingness to Pay for Reusable Bags in Chatime - Kamila, Refa Aisa; Fadjar, Nurman Setiawan (Journal of Development Economic and Social Studies, 2025)
The use of reusable bags has been proven to reduce the volume of single-use plastic waste (SUPB). This study analyzes the Willingness to Pay (WTP) and the factors that affect WTP for the use of reusable bags when going shopping at Chatime Soehat Corner, Malang City. The research methods used are descriptive analysis, Contingent Valuation Method (CVM), and binary logistic regression, with data collection was done by distributing questionnaires. The results of the descriptive analysis show that the majority of respondents are female, aged 20–30, with an income of less than Rp 1,500,000, and are unemployed. The WTP values obtained through CVM analysis revealed that the majority of respondents chose Rp 2,000 as the maximum price, with an average resulting in Rp 3,935. In other words, the factors significantly affecting WTP are price perception and consumer lifestyle, while income and knowledge do not have a significant effect. The implications of this study reveal consumers' willingness to pay more for reusable bags, which can be utilized by the government and business actors to support sustainable industries. By implementing reusable bags as a replacement for Single-Use Plastic Bags (SUPB), this policy can lead to a reduction in plastic waste.